Arenavirus Stable Signal Peptide Is the Keystone Subunit for Glycoprotein Complex Organization - Bederka, Lydia H.; Bonhomme, Cyrille J.; Ling, Emily L.; Buchmeier, Michael J. (mBio, 2014)
The rodent arenavirus glycoprotein complex encodes a stable signal peptide (SSP) that is an essential structural component of mature virions. The SSP, GP1, and GP2 subunits of the trimeric glycoprotein complex noncovalently interact to stud the surface of virions and initiate arenavirus infectivity. Nascent glycoprotein production undergoes two proteolytic cleavage events: first within the endoplasmic reticulum (ER) to cleave SSP from the remaining precursor GP1/2 (glycoprotein complex [GPC]) glycoprotein and second within the Golgi stacks by the cellular SKI-1/S1P for GP1/2 processing to yield GP1 and GP2 subunits. Cleaved SSP is not degraded but retained as an essential glycoprotein subunit. Here, we defined functions of the 58-amino-acid lymphocytic choriomeningitis virus (LCMV) SSP in regard to glycoprotein complex processing and maturation. Using molecular biology techniques, confocal microscopy, and flow cytometry, we detected SSP at the plasma membrane of transfected cells. Further, we identified a sorting signal (FLLL) near the carboxyl terminus of SSP that is required for glycoprotein maturation and trafficking. In the absence of SSP, the glycoprotein accumulated within the ER and was unable to undergo processing by SKI-1/S1P. Mutation of this highly conserved FLLL motif showed impaired glycoprotein processing and secretory pathway trafficking, as well as defective surface expression and pH-dependent membrane fusion. Immunoprecipitation of SSP confirmed an interaction between the signal peptide and the GP2 subunit; however, mutations within this FLLL motif disrupted the association of the GP1 subunit with the remaining glycoprotein complex. IMPORTANCE Several members of the Arenaviridae family are neglected human pathogens capable of causing illness ranging from a nondescript flu-like syndrome to fulminant hemorrhagic fever. Infections by arenaviruses are mediated by attachment of the virus glycoprotein to receptors on host cells and virion internalization by fusion within an acidified endosome. SSP plays a critical role in the fusion of the virus with the host cell membrane. Within infected cells, the retained glycoprotein SSP plays a neglected yet essential role in glycoprotein biosynthesis. Without this 6-kDa polypeptide, the glycoprotein precursor is retained within the endoplasmic reticulum, and trafficking to the plasma membrane where SSP, GP1, and GP2 localize for glycoprotein assembly into infectious virions is inhibited. To investigate SSP contributions to glycoprotein maturation and function, we created an SSP-tagged glycoprotein to directly detect and manipulate this subunit. This resource will aid future studies to identify host factors that mediate glycoprotein maturation. Several members of the Arenaviridae family are neglected human pathogens capable of causing illness ranging from a nondescript flu-like syndrome to fulminant hemorrhagic fever. Infections by arenaviruses are mediated by attachment of the virus glycoprotein to receptors on host cells and virion internalization by fusion within an acidified endosome. SSP plays a critical role in the fusion of the virus with the host cell membrane. Within infected cells, the retained glycoprotein SSP plays a neglected yet essential role in glycoprotein biosynthesis. Without this 6-kDa polypeptide, the glycoprotein precursor is retained within the endoplasmic reticulum, and trafficking to the plasma membrane where SSP, GP1, and GP2 localize for glycoprotein assembly into infectious virions is inhibited. To investigate SSP contributions to glycoprotein maturation and function, we created an SSP-tagged glycoprotein to directly detect and manipulate this subunit. This resource will aid future studies to identify host factors that mediate glycoprotein maturation.